Policy and regulatory measures supporting the implementation of nature-based solutions in urban stormwater management of private properties: Insights from Finland - Saarinen, Aino; Leskinen, Piia; Reini, Aleksi; Fagerholm, Nora; Kasvi, Elina (Springer Nature, 2026)
Despite widely existing consensus that nature-based solutions (NbS) provide competitive and sustainable alternatives for grey infrastructure in urban water management, the implementation of NbS is lagging behind current needs. This study explores if and how regulatory measures can promote NbS adoption on privately owned land. Policy document analysis of Finnish stormwater programmes gathers how NbS are considered at municipal-level, key informant interviews aim to identify bottlenecks in stormwater regulations, and building permit analysis evaluates whether policy instruments have increased NbS implementation on private land. Results reveal fragmented municipal regulations due to a lack of national consensus, leading to bottlenecks for implementation such as limited knowledge, commitment, and institutional coherence. While current regulations have increased solution diversity, widespread NbS implementation requires mandating and consistent regulations aligned with sustainability goals, improved understanding of NbS functionality, examples and education, national cooperation, and recognition of NbS as viable stormwater management options.